Cytotoxicity and Structural Analyses of 2, 2′‐Bipyridine‐, 4, 4′‐Dimethyl‐2, 2′‐bipyridine‐ and 2‐(2′‐Pyridyl)quinoxalineplatinum(II) Complexes (Eur. J. Inorg. Chem. 25/2015). Issue 25 (September 2015) - Pages, Benjamin J.; Zhang, Yingjie; Li, Feng; Sakoff, Jennette; Gilbert, Jayne; Aldrich‐Wright, Janice R.
Abstract : The cover picture shows X‐ray crystal structures contrasting the differences in stacking and coordination geometry of platinum(II) complexes of 4, 4'‐dimethyl‐2, 2'‐bipyridine and 2‐(2'‐pyridyl)quinoxaline. The CD spectra emphasise the effect that such structural differences can have upon the electronic properties of the compounds. Fluorescently stained HT29 human colon carcinoma cells make up the background, demonstrating the application of the complexes as anticancer agents. Finally, the Southern Cross refers to the country of origin of this work, while the yellow stars represent our acknowledgement to this journal and the European Union. Details are discussed in the article by J. R. Aldrich‐Wright et al. onp. 4167 ff . For more on the story behind the cover research, see theCover Profile .